A literatura infantil de temática africana e afro-brasileira nos acervos complementares (PNLD 2013-2015) - Silva, Sheila Dias da (2020)
The objective of this study is to analyze the literary works that focus on African and / or AfroBrazilian History and Culture selected by MEC and that are part of the boxes sent to schools in the first cycle of Basic Education. The Acervos Complementares: alfabetização e letramento nas diferentes áreas do conhecimento (Complementary Collections: literacy in different areas of knowledge or PNLD 2013) are books that were delivered by the federal government with the aim of assisting the teacher and guaranteeing the processes of literacy of young children in those school phases. Unlike other programs that send literary works for collective use, in school libraries, those specific collections remain in the classroom. Of the 180 works that comprise the Acervos, only 17 have black characters as protagonists and they make up our corpus. Therefore, the intention is to demonstrate the extent to which the authors of those works use their narratives to promote and value African and Afro-descendant culture and / or whether there are still traces of a Eurocentric bias in them. In a critical approach, I investigate how issues such as race, identity, belongings, displacements and cultural negotiations are dealt with in those narratives. This research takes place according the approach of post-colonial and decolonial studies. As a result, I note that many of the literary narratives analyzed here break with the Eurocentric bias of works belonging to children’s literary canon, however, in some cases, some traces of the standard hegemonic discourse still remain. Thus, I believe that it is through the teacher's intervention process, as he or she comes to know those texts, that this structure can be broken.